Identification of UCP1 and UCP2 as Potential Prognostic Markers in Breast Cancer: A Study Based on Immunohistochemical Analysis and Bioinformatics - Yu, Xin; Shi, Manman; Wu, Qi; Wei, Wen; Sun, Shengrong; Zhu, Shan (Frontiers in Cell and Developmental Biology, 2022)
Background Uncoupling protein 1 (UCP1) and UCP2 are associated with tumor metabolism and immunity. However, the prognostic value and molecular mechanisms underlying their action in breast cancer (BC) remain unclear. Material and methods In TCGA-BRCA cohort, we investigated the expression characteristics of UCP mRNAs, analyzed their prognostic value by Kaplan-Meier survival analysis, their potential molecular functions by gene set enrichment analysis, and their relationship with immune infiltrating cell types using TIMER and CIBERSORT, along with the assessment of their association with mutational profiles. Kaplan-Meier survival analysis was performed for UCPs in our cohort and their association with BC thermogenesis was assessed by thermal tomography. Results High expression of UCP1 and UCP2 were positive prognostic markers for BC. UCP1 was associated with the impaired glucose metabolism, while UCP2 with enhanced anti-tumor immunity. High expressions of UCP1 and UCP2 were associated with CDH1 mutations. High UCP1 expression was associated with a high rate of thermogenesis in BC. Conclusions These results implied a key role of UCP1 and UCP2 in prognosis, metabolism, and immune infiltration in BC. Further investigation of the relevant molecular mechanisms may provide new strategies for BC treatment.